2001
DOI: 10.1080/009841001459405
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Organophilic Montmorillonite Clay Inclusion in Zearalenone-Contaminated Diets Using the Mouse Uterine Weight Bioassay

Abstract: Previous studies with low-pH montmorillonite (LPHM) clay exchanged with alkylammonium compounds showed that these organo clays were quite effective in sorbing the estrogenic mycotoxin zearalenone (ZEN) from aqueous solution. The potential toxicity of these types of clays, in particular hexadecyltrimethylammonium (HDTMA) LPHM, led to the investigation of the sorption efficacy of clay exchanged with a less toxic primary amine analog, hexadecylamine (HDA). Isothermal analysis studies showed that HDA LPHM was able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 17 publications
1
36
1
Order By: Relevance
“…Clays added to a diet can bind and immobilize toxic materials in the gastro-intestinal tract of animals and largely reduce their biological availability and toxicity for the body (Phillips, 1999;Lemke et al, 2001;Phillips et al, 2002;Trckova et al, 2004). Multiple studies have confirmed the decontaminating properties of clay minerals.…”
Section: Adsorption Capacity and Effects Of Clay Mineralsmentioning
confidence: 92%
“…Clays added to a diet can bind and immobilize toxic materials in the gastro-intestinal tract of animals and largely reduce their biological availability and toxicity for the body (Phillips, 1999;Lemke et al, 2001;Phillips et al, 2002;Trckova et al, 2004). Multiple studies have confirmed the decontaminating properties of clay minerals.…”
Section: Adsorption Capacity and Effects Of Clay Mineralsmentioning
confidence: 92%
“…Average uterine weight was significantly greater in E2-␤-treated animals than in control animals (E2-␤, 0.562 Ϯ 0.011 vs. controls, 0.097 Ϯ 0.005 g; n ϭ 12 animals). Increased uterine weight has been previously used as an indicator of E2-␤ treatment (14,31,39).…”
Section: Resultsmentioning
confidence: 99%
“…To avoid decreases in hematocrit during the experimental period, red blood cells were resuspended in saline and infused back into the animal after each sample collection. Uterine weight was measured as an indicator of E2-␤ delivery (14,31,39). At the final time point, blood gases were measured to confirm exposure conditions using a blood gas analyzer (model ABL-5, Radiometer).…”
Section: Methodsmentioning
confidence: 99%
“…The powder was prepared according to the method described by previous study [33]. The HNTs were modified using SKC (Jingwei Chemical Co., Ltd., Shanghai, China) according to the methods described previously [34].…”
Section: Sorbent Materials and Modificationmentioning
confidence: 99%